The Influence of Intelectual Capital toward Profitability of Indonesian Banking Sector in 2004 - 2008 - Any Eliza (Politeknik Negeri Lampung, 2011)
This research attempts to investigate empirically the impact of intellectual capital measured by value creation efficiency of intellectual capital and capital employed on profitability measured by ROA. This research uses financial and capital market data of 120 banks listed on Indonesia Stock Exchange from 2004 to 2008. Empirical analysis is conducted using multiple linear regression. Findings from empirical analysis indicate that value creation efficiency of capital employed and human capital have a positive impact on ROA; value creation efficiency of structural capital has a negative impact on ROA Key words: intellectual capital, ROA, bank, Indonesia Stock Exchange